LIN28A-dependent lncRNA NEAT1 aggravates sepsis-induced acute respiratory distress syndrome through destabilizing ACE2 mRNA by RNA methylation - Jun Liu; Xiang Li; Peng Yang; Yufeng He; Weilong Hong; Yawei Feng; Zhiqiang Ye (Journal of Translational Medicine)
Abstract Background Acute respiratory distress syndrome (ARDS) is a life-threatening and heterogeneous disorder leading to lung injury. To date, effective therapies for ARDS remain limited. Sepsis is a frequent inducer of ARDS. However, the precise mechanisms underlying sepsis-induced ARDS remain unclear. Methods Here RNA methylation was detected by methylated RNA immunoprecipitation (MeRIP), RNA stability was determined by RNA decay assay while RNA antisense purification (RAP) was used to identify RNA-protein interaction. Besides, co-immunoprecipitation (Co-IP) was utilized to detect protein-protein interaction. Moreover, mice were injected with lipopolysaccharide (LPS) to establish sepsis-induced ARDS model in vivo. Results This study revealed that long non-coding RNA (lncRNA) nuclear-enriched abundant transcript 1 (NEAT1) aggravated lung injury through suppressing angiotensin-converting enzyme 2 (ACE2) in sepsis-induced ARDS models in vitro and in vivo. Mechanistically, NEAT1 declined ACE2 mRNA stability through heterogeneous nuclear ribonucleoprotein A2/B1 (hnRNPA2B1) in lipopolysaccharide (LPS)-treated alveolar type II epithelial cells (AT-II cells). Besides, NEAT1 destabilized ACE2 mRNA depending on RNA methylation by forming methylated NEAT1/hnRNPA2B1/ACE2 mRNA complex in LPS-treated AT-II cells. Moreover, lin-28 homolog A (LIN28A) improved NEAT1 stability whereas insulin-like growth factor 2 mRNA binding protein 3 (IGF2BP3) augmented NEAT1 destabilization by associating with LIN28A to disrupt the combination of LIN28A and NEAT1 in LPS-treated AT-II cells. Nevertheless, hnRNPA2B1 increased NEAT1 stability by blocking the interaction between LIN28A and IGF2BP3 in LPS-treated AT-II cells. Conclusions These findings uncover mechanisms of sepsis-triggering ARDS and provide promising therapeutic targets for sepsis-induced ARDS.